2018
DOI: 10.1103/physrevb.98.020401
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal spin Seebeck effect in antiferromagnets

Abstract: We theoretically propose a nonreciprocal spin Seebeck effect, i.e., nonreciprocal spin transport generated by a temperature gradient, in antiferromagnetic insulators with broken inversion symmetry. We find that nonreciprocity in antiferromagnets has rich properties not expected in ferromagnets. In particular, we show that polar antiferromagnets, in which the crystal lacks the spatial inversion symmetry, exhibit perfect nonreciprocityone-way spin current flow irrespective of the direction of the temperature gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
(50 reference statements)
1
22
0
Order By: Relevance
“…In such situations, however, the magnon excitations in the antiferromagnet can contribute to the thermal transport. In particular, it was shown that the Dzyaloshinskii-Moriya interaction on the second-neighbor bonds leads to nonlinear thermal transport [45][46][47]. However, as the Dzyaloshinskii-Moriya interaction arises from the spin-orbit coupling, one may suppress the magnon contribution by choosing the antiferromagnets with less spin-orbit coupling.…”
Section: Contributions From Magnonsmentioning
confidence: 99%
“…In such situations, however, the magnon excitations in the antiferromagnet can contribute to the thermal transport. In particular, it was shown that the Dzyaloshinskii-Moriya interaction on the second-neighbor bonds leads to nonlinear thermal transport [45][46][47]. However, as the Dzyaloshinskii-Moriya interaction arises from the spin-orbit coupling, one may suppress the magnon contribution by choosing the antiferromagnets with less spin-orbit coupling.…”
Section: Contributions From Magnonsmentioning
confidence: 99%
“…Although they were mainly studied for ferromagnetic slabs [48,49] and for magnetic orderings in the noncentrosymmetric crystals [50,51,59,71,72], where the magnetic dipolar interaction and/or the Dzyaloshinskii-Moriya (DM) interaction are important [73,74], it was shown that they occur even via other mechanisms, such as frustrated exchange interactions [75,76] and bond-dependent symmetric exchange interactions [77,78]. The nonreciprocal magnons have a potential to exhibit further intriguing nonreciprocal phenomena, such as the magneto-optical effect [79][80][81] and spin Seebeck effect [82], which avoid Joule heating.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, several proposals to rectify the spin currents in magnets have been put forward. [ 16–20 ] For example, it was shown that in a magnetic insulator with anisotropic exchange interaction the spin current can be manipulated by tuning the magnetic field. [ 16 ] Moreover, rectification of spin currents generated via the spin Seebeck effect has been reported in some recent works, [ 17,18 ] where the rectification lies in the fact that the systems exhibit asymmetry in the spectrum of magnetic excitations or in the structure.…”
Section: Introductionmentioning
confidence: 99%